Supervision of Stay Permits for Foreign Citizens in the Legal Area of the TPI Gorontalo Class I Immigration Office - Wahab, Ramla; Darmawati, Darmawati; Sumiyati, Sumiyati (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The authority to take immigration action regarding the expiration of a limited stay permit based on Article 53 of Law Number 6 of 2011 concerning Immigration in the Gorontalo City immigration area is the responsibility of the TPI Gorontalo Class I Immigration Office. The problem in this research is how to monitor and take action against foreign nationals who violate their residence permit (overstay) at the TPI Gorontalo Class I Immigration Office. The research method uses a normative and empirical juridical approach, the data used is secondary data and primary data. The study was carried out using literature and field studies, the data analysis used was qualitative. The results of the research show that the implementation of supervision and action against foreign nationals who violate residence permits (overstay) at the TPI Gorontalo Class 1 Immigration Office, enforcement of immigration law, especially regarding the issue of misuse of visas, the immigration authorities should apply cumulative criminal sanctions against perpetrators of criminal acts, namely the imposition of prison sentences. In accordance with the applicable provisions of the Immigration Law, after the perpetrator of a criminal offense has served his criminal sentence, the next action taken by the immigration authorities is to carry out administrative immigration action, namely deporting the foreign national